Computer science and engineering : proceedings of the International Conference on Computational Science and Engineering (Beliaghata, Kolkata, India, 4-6 October 2016) /: proceedings of the International Conference on Computational Science and Engineering (Beliaghata, Kolkata, India, 4-6 October 2016). (2016) - Unknown
No abstract available